Spiritual And Educational Sphere And National Values: Interaction And Impact On The Cultural Development Of The New Uzbekistan - Khojalepesov Polat Zinatdinovich; Ubbiniyazov Muratbek Azat ulı; Dawletbaev Zafar Dawletbaevich; Mirzabaeva Ulzada Quwanishbaevna; Mambetsharipova Gulzada Polatbaevna (Peerian Journals Publishing, 2024)
This article explores the importance of preserving and promoting national values in the context of spiritual and educational sphere. The authors analyse the impact of national values on various aspects of cultural development, including literature, art, education and social values. The article also considers modern challenges and opportunities faced by national values in the context of globalization and cultural diversity. The results of the study underline the importance of dialogue and cooperation between different cultures for the sustainable development of the spiritual and educational sphere and the preservation of national values
Keywords: spirituality; educational; sphere; Judith